Naturalisation d’Anredera cordifolia (Basellaceae) en Algérie - N. Sakhraoui; S. Metallaoui; A. Chefrour (My University, 2021)
The occurrence and actual status of Anredera cordifolia (Basellaceae) in Algeria is here reported, for the first time. The species has been recorded in many localities within Skikda area. It is the only representative of Basellaceae in the whole country. Maintained in observation area within the native flora for many years, the plant could be considered as naturalized.